1983
DOI: 10.1128/jcm.18.5.1122-1126.1983
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of in vitro susceptibility tests for detecting coagulase-negative staphylococcal resistance to penicillinase-resistant semisynthetic penicillins

Abstract: The reliabilities of five in vitro susceptibility tests (agar dilution, broth microdilution, automated MS-2, Kirby-Bauer disk diffusion, and ability to grow on methicillin-containing agar) to predict the susceptibility of 204 coagulase-negative staphylococcal isolates to penicillinase-resistant semisynthetic penicillins were compared. There was wide variation in susceptibility, with results ranging from 86.3% susceptible by MS-2 to 38.2% by growth on methicillin-containing agar. The results of the broth diluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1985
1985
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…We also found that significantly more resistant strains were detected after 48 h than after 24 h of incubation with cation-supplemented MH broth plus 2% NaCl. This increased detection with prolonged incubation has been noted by others working mainly with coagulase-negative staphylococci (2,19). Another interesting observation, and one for which we have no explanation, is that significantly fewer resistant strains were identified at 24 h when cationsupplemented MH broth was used in MIC trays (phase 1 versus phase 2).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…We also found that significantly more resistant strains were detected after 48 h than after 24 h of incubation with cation-supplemented MH broth plus 2% NaCl. This increased detection with prolonged incubation has been noted by others working mainly with coagulase-negative staphylococci (2,19). Another interesting observation, and one for which we have no explanation, is that significantly fewer resistant strains were identified at 24 h when cationsupplemented MH broth was used in MIC trays (phase 1 versus phase 2).…”
Section: Resultssupporting
confidence: 64%
“…In recent years, however, Staphylococcus epidermidis has been recognized as a pathogen with increased frequency, especially in patients with indwelling foreign devices (2, 3, 12, 16) and in immunosuppressed (10, 33) and leukopenic (31) patients. It has been suggested that S. epidermidis may not behave exactly as S. aureus in susceptibility testing because the proportion of resistant organisms per isolate is lower for S. epidermidis (19). The purpose of our study, therefore, was to determine whether methods recommended for detecting methicillin-resistant S. aureus are equally applicable to S. epidermidis.…”
mentioning
confidence: 97%